Etica reprezentației teatrale și limitele libertății creatoare - Vasiniuc, Tiberius (Theatrical Research, 2023)
The Ethics of Theatrical Performance Theatre represents an ingenuous form of dialogue of the self with another, a space of contradiction between freedom and alienating forms of power. By opening paths of ethics, the performing arts impose or are imposed on themselves limits that the stage performance itself continues to interrogate. Are there ways or means to sign an “agreement” between the stage creators and the audience, between the creation and the spectators, in such a way that, without infringing the right to freedom of the artists, the feelings, convictions, or beliefs of the receivers are not adversely affected? The answer comes from the very relationship that the theatre has with itself, from the way the creators understand how to manage sensitive subjects, approaching and not ignoring them, but passing them through the filter of responsibility regarding the mission of art and the significant role which the encounter has. In contemporary theatre, there are taboo or controversial topics (for example, the representation of violence and trauma) that attract more attention than ever and continue to be perceived as sensitive depending on the cultural, social or political context in which they are presented. Thus, the limit becomes a central notion that we cannot avoid in the discussions related to the role that the theatre plays in relation to the spectators and their sufferings or sensitivities.